Entre o tempo e o espaço: as relações de identidade social na escrita de Lima Barreto e no rap de Emicida - Laeber, Ana Paola (2023)
In the context of 20th-century Brazilian modernity, marked by social changes and intense debates on ethnic issues, racist theories propagated the idea of natural and biological differences among human groups, using science to justify the alleged inferiority of certain ethnic groups, such as the Black population. This drove the analysis of the identity of socially marked groups in cultural and social studies. This study focuses on the analysis of the lack of citizenship generated by racism, establishing connections between the literary works of Lima Barreto, including Diário Íntimo and Diário do Hospício (posthumously published in 1956), and the musical compositions “Boa Esperança” and “Mandume” from the album Sobre Crianças, Quadris, Pesadelos e Lições de Casa... (2015) by Leandro Roque de Oliveira, known as Emicida. The research also adopts a theoretical approach that explores the social and geographical spaces that influenced these writers, considering the historical contexts of segregation and marginalization they faced. Although Lima Barreto and Emicida belong to different periods and contexts, this study proposes a spiral and dialogical analysis of the representations and identity reconstructions present in their works. The research aims to shed light on the intersections between literature, music, and identity, exploring how these two artists addressed issues of citizenship and racism in their respective works, incorporating the insights of renowned scholars such as Abdias do Nascimento, Carmen Lúcia Negreiros de Figueiredo, Kabengele Munanga, Lilia Moritz Schwarz and Stuart Hall, among others.